Proteomic Analysis Reveals a Biofilm-Like Behavior of Planktonic Aggregates of Staphylococcus epidermidis Grown Under Environmental Pressure/Stress - Bottagisio, Marta; Soggiu, Alessio; Piras, Cristian; Bidossi, Alessandro; Greco, Viviana; Pieroni, Luisa; Bonizzi, Luigi; Roncada, Paola; Lovati, Arianna B. (Frontiers in Microbiology, 2019)
Prosthetic joint replacement failure has a huge impact on quality of life and hospitalization costs. A leading cause of prosthetic joint infection is bacteria-forming biofilm on the surface of orthopedic devices. Staphylococcus epidermidis is an emergent, low-virulence pathogen implicated in chronic infections, barely indistinguishable from aseptic loosening when embedded in a mature matrix. The literature is scarce on the behavior of quiescent S. epidermidis in mature biofilms. To fill this gap, we performed comparative analysis of the whole proteomic profiles of two methicillin-resistant S. epidermidis strains growing in planktonic and in sessile form to investigate the molecular mechanisms underlying biofilm stability. After 72-h culture of biofilm-forming S. epidermidis, overexpression of proteins involved in the synthesis of nucleoside triphosphate and polysaccharides was observed, whereas planktonic bacteria expressed proteins linked to stress and anaerobic growth. Cytological analysis was performed to determine why planktonic bacteria unexpectedly expressed proteins typical of sessile culture. Images evidenced that prolonged culture under vigorous agitation can create a stressful growing environment that triggers microorganism aggregation in a biofilm-like matrix as a mechanism to survive harsh conditions. The choice of a unique late time point provided an important clue for future investigations into the biofilm-like behavior of planktonic cells. Our preliminary results may inform comparative proteomic strategies in the study of mature bacterial biofilm. Finally, there is an increasing number of studies on the aggregation of free-floating bacteria embedded in an extracellular matrix, prompting the need to gain further insight into this mode of bacterial growth.